THE FUNCTIONAL BASIS OF BUSINESS WHOLESALE TRADE ENTERPRISES IN MODERN CONDITIONS - Andrey N. Vashchekin (Статистика и экономика)
In order to live successfully in the wholesale market, the company must carefully analyze its functions performed in this market, while constantly seeking to supplement the list of services provided with it, and in any case not allowing reduction of the list, varying amounts of their services based on customer requests.